Weeds — powerful competitors for young plants the willow rootworm Salix viminalis L. - Gavrylyuk, L.; Nemchenko, A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
To reduce destructive anthropogenic pressure on the environment, modern energy envisages the widespread use of bioenergy raw materials. The article is devoted to the perspective of the species of bioenergetic cultures in the West Forest-steppe region — the willow rootworm — Salix viminalis L. The author’s focuses on the most acute problem in the technology of growing this crop — the need to protect young plants in the first year of vegetation from weeds.